Hydroxamate HDAC inhibitors potency in mediating dentine regeneration: a review - Sulistyowati, I; Anggraini, W; Ariyani, A P; Khalid, Rafiq (CRC Press, Taylor & Francis Group, 2024)
The quality of the reparative dentin structure is influenced by the signaling molecules contained in the pulp-capping material applied. A tunnel defect has been found in reparative dentin under treatment with conventional pulp-capping materials. It led to treatment failure due to the reduction of dentine permeability. Moreover, HDAC inhibitors, epigenetic modifying agents, have been reported to induce odontoblast-like differentiation and mineralization. This article aims to observe the potency of HDAC inhibitors (HDACis) in dentin regeneration. This article reviews the latest improvement in the field of dentine regeneration with the involvement of epigenetic-modifying agents such as HDAC inhibitors (HDACis). Trichostatin A (TSA) and suberoylanilide hydroxamic acid (SAHA or vorinostat), grouped in the hydroxamates family, induce the expression of a series of odontogenic-related genes and lead to mineralization. This article provides a theoretical basis for understanding how reparative dentin is formed and mediated by signaling molecules and describes how these HDACis epigenetically induce odontoblast-like differentiation.